Effect of flavonoid compound preservatives on the postharvest quality of banana - ZENG Jun; YANG Jiali; YANG Bao; ZHU Hong (浙江大学学报. 农业与生命科学版, 2020)
Harvested banana fruit was treated by a mixed solution of morin and luteolin (in a mass ratio of 1∶2), and the combined effect on quality maintenance and shelf life of banana was investigated. The results showed that the combined treatment significantly delayed the ripening process, effectively reduced crown rot, maintained the appearance including color and firmness, reduced the respiratory rate and delayed the emergence of ethylene release and respiratory peak. The data from nuclear magnetic resonance (NMR) spectroscopy of the peel revealed the composition and level of metabolites during the banana ripening and senescence. Principal component analysis reflected that the first principal components were carbohydrates, free amino acids and other organic components such as ethanol. In a word, the combined treatment of morin and luteolin effectively delays the changes of metabolite profiles, thus maintains the fruit quality and delays senescence. As flavonoids are natural plant metabolites, which are safe, non-toxic and cost-effective, so they have the potential to be developed into broad-spectrum fruit preservatives.